2015
DOI: 10.1111/hex.12369
|View full text |Cite
|
Sign up to set email alerts
|

Does a decision aid for prostate cancer affect different aspects of decisional regret, assessed with new regret scales? A randomized, controlled trial

Abstract: Objective To develop and validate new regret scales and examine whether a decision aid affects different aspects of regret in the treatment choice for prostate cancer.Methods This was a multicentre trial (three sites) with imbalanced randomization (1 : 2). From 2008 to 2011, patients with localized prostate cancer were randomized 1 : 2 to usual care (N = 77) or usual care plus a decision aid presenting risks and benefits of different treatments (N = 163). The treatments were surgery and (external or interstiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
(85 reference statements)
1
32
0
Order By: Relevance
“…The urologist could provide decision aids for those patients not able to make a treatment choice, especially those with comorbidities, given that the use of the decision aids was not previously found to have been associated with decisional regret [18]. The decision aids should not only provide information but also facilitate shared decision-making [19].…”
Section: Discussionmentioning
confidence: 99%
“…The urologist could provide decision aids for those patients not able to make a treatment choice, especially those with comorbidities, given that the use of the decision aids was not previously found to have been associated with decisional regret [18]. The decision aids should not only provide information but also facilitate shared decision-making [19].…”
Section: Discussionmentioning
confidence: 99%
“…The DRS has been applied in observational studies, for example, demonstrating that higher physician empathy predicts lower decision regret in people with cancer or patients with cancer . The DRS has also been used in randomized controlled trials of decision aids which recently have been shown to reduce decisional conflict . Indeed, decision regret often reaches high levels (increasing 6 months or more after a decision) due to very poor outcomes and definitive knowledge about the outcome .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The DRS has also been used in randomized controlled trials of decision aids which recently have been shown to reduce decisional conflict. [7][8][9] Indeed, decision regret often reaches high levels (increasing 6 months or more after a decision) due to very poor outcomes and definitive knowledge about the outcome. 10 Several risk factors have been identified as temporal predictors for decisional regret including decisional conflict, unmet information needs, serious adverse physical health outcomes and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…One item was added to assess satisfaction with participation in decision‐making. Decisional regret was measured using the Brehaut Regret Scale and a new regret scale, which measures three different aspects of decisional regret: process, option, and outcome regret .…”
Section: Methodsmentioning
confidence: 99%